SELEBRITI YANG SUDAH MENINGGAL (DEAD CELEBRITY ENDORSER,) PENGARUHNYA TERHADAP KEPUTUSAN PEMBELIAN, BRAND IMAGE DAN BRAND PERSONALITY (Studi Pada KukuBima Ener-G Mbah Maridjan) - Siti Hartini Yulianti; Arief Budiman; Ahmad Rifani (Universitas Lambung Mangkurat, 2016)
This study to identify and analyze the influence of the dead celebrity endorser is measured through expertise, trustworthines, attractiveness, reputation, hero and devoted admirer on decision purchasing, brand image and brand personality KukuBima Ener-G Mbah Maridjan. Methods of data collection in this study using questionnaires with 100 consumers KukuBima Ener-G as a sample. Measurement of variables using techniques Likert Scale. Determine the effect of variables using a statistical technique Structural Equation Modeling with Partial Least Square (PLS) were processed with the SmartPlS program.The results of this study indicate that dead celebrity endorser influence significantly on purchasing decisions, brand image and brand personality KukuBima Ener-G Mbah Maridjan. The results also show that brand image and brand personality KukuBima Ener-G influence significantly on purchasing decisions.